Analysis of Access to Reproductive Health Services for the Elderly Challenges of Stigma and Policy in Indonesia - Rahmah Juliani Siregar; Elvi Suryani; Maryam Latifah Harahap; Juliana Lubis; Lena Juliana Harahap (The Indonesian Institute of Science and Technology Research, 2026)
This qualitative study examines the barriers faced by elderly populations in Indonesia in accessing reproductive health services, focusing on cervical and prostate cancer screening, sexuality counseling, and menopause/andropause management. Despite the increasing number of older adults, reproductive health services remain predominantly oriented toward younger groups, leaving elderly needs under-addressed. Using semi-structured interviews with 35 elderly individuals, 15 healthcare providers, and 10 policymakers across urban and rural settings, the study identifies significant structural and cultural challenges. Key findings reveal pervasive social stigma surrounding elderly sexuality, inadequate healthcare provider training, and fragmented policy frameworks that fail to explicitly include geriatric reproductive health. Rural participants reported limited availability of essential screenings and counseling services, while many providers perceived elderly reproductive health concerns as low priority. Policy analysis highlights the absence of comprehensive guidelines and inconsistent implementation across regions. These barriers contribute to disparities in service utilization and negatively impact elderly health outcomes. The study recommends evidence-based strategies including stigma reduction initiatives, integration of reproductive health services into primary care for the elderly, enhanced provider education, and the development of targeted policies with dedicated funding. Addressing these challenges is critical to promoting equitable access to reproductive healthcare for Indonesia’s aging population, supporting their right to health and well-being. This research contributes to filling the gap in geriatric reproductive health literature and offers practical policy recommendations to improve service delivery in Indonesia.